2022
DOI: 10.1111/jcal.12705
|View full text |Cite
|
Sign up to set email alerts
|

The didactic and pedagogical design of e‐learning in higher education: A systematic literature review

Abstract: Background: Since about 2010 e-learning has been embedded in educational practice and has become, surely due to the Covid-19 pandemic, increasingly important.Objectives: Although much has been written about e-learning, little is known about crucial didactic and pedagogical design principles for e-learning. This review tried to fill that gap.Methods: Based on a systematic literature review, 42 studies (out of 1857 unique hits) were included that address e-learning design in higher education. Open and axial codi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 61 publications
1
9
0
Order By: Relevance
“…The columns represent the endoge- We found that the use of scaffolding strategies in mobile-based assessment systems has a positive effect on students' learning performance (hypothesis H 1a ). This result corroborates the findings of other researchers that noted the importance of content and process scaffolding in the didactic and pedagogic design of e-learning (Theelen & van Breukelen, 2022), and the effectiveness of mobile-based scaffolding for supporting student performance in vocabulary and conversation comprehension in EFL settings (Fang et al, 2021). Moreover, this result concur with previous studies in terms of the positive influence of scaffolding on students' learning performance (Bacca-Acosta et al, 2021;Belland et al, 2015;Belland, 2017;Guo et al, 2022;Jabeen et al, 2021;Lee et al, 2021).…”
Section: Predictive Relevance Of the Structural Modelsupporting
confidence: 91%
“…The columns represent the endoge- We found that the use of scaffolding strategies in mobile-based assessment systems has a positive effect on students' learning performance (hypothesis H 1a ). This result corroborates the findings of other researchers that noted the importance of content and process scaffolding in the didactic and pedagogic design of e-learning (Theelen & van Breukelen, 2022), and the effectiveness of mobile-based scaffolding for supporting student performance in vocabulary and conversation comprehension in EFL settings (Fang et al, 2021). Moreover, this result concur with previous studies in terms of the positive influence of scaffolding on students' learning performance (Bacca-Acosta et al, 2021;Belland et al, 2015;Belland, 2017;Guo et al, 2022;Jabeen et al, 2021;Lee et al, 2021).…”
Section: Predictive Relevance Of the Structural Modelsupporting
confidence: 91%
“…E-learning tools comprise education methods, including e-mail, Microsoft Teams, Skype, Zoom, WhatsApp, and learning management systems such as Moodle. [67] Thus far, e-learning using digital tools has been implemented for oral hygiene to improve plaque removal and gingivitis. [14] Moreover, there have been reports on various kinds of e-learning using the internet.…”
Section: Discussionmentioning
confidence: 99%
“…E-learning tools comprise education methods, including e-mail, Microsoft Teams, Skype, Zoom, WhatsApp, and learning management systems such as Moodle. [ 67 ]…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…All that has been mentioned about the importance of teacher training is supported by the research conducted by [15] which indicates that well-designed didactic and pedagogical elearning in higher education can positively contribute to student learning outcomes; it also offers several advantages in the process, such as greater flexibility and accessibility, personalized learning, and the ability to engage students in collaborative activities. However, it is important to highlight several challenges, such as the need for adequate technical support, appropriate course design, and effective communication with students.…”
Section: Introductionmentioning
confidence: 98%